Case Study : Aci Jaya Enterprise / Nuraiman Syahira Asraae - Asraae, Nuraiman Syahira (2021)
Based on Fundamentals of Entrepreneurship (ENT300) course requirement, I need to carry out a case study. For the case study, I need to find a company that their sales did not exceed RM250000 in a year and then collect all the information about a company to complete this case study. So, the company that I choose for this case study is Aci Jaya Enterprise which is located at Tanah Merah, Kelantan. I also have decided to contact Aci Jaya Enterprise owner which is Puan Aminah binti Che Ibrahim to do an online interview session. It is to evaluate the business performance and try to get much information. After the online interview session, I have known a little bit about the company’s background, sales, employees, product and many more. The company sale in a year is RM120000. Other than that, I also have known a little bit about the owner’s profile and her entrepreneurial characteristics from the online interview session. So, in this case study, I will explain more about Aci Jaya Enterprise and also the owner, Puan Aminah binti Che Ibrahim entrepreneurial characteristics.